HANDLING OF PURSE SEINE CAPTURE CATCHING FOR KM. SINAR HARAPAN – 05 IN THE NUSANTARA FISHERIES PORT (PPN) SIBOLGA - Suci Asrina Ikhsan; Muhammad Nur Arkham; Anderson Foresta (JURNAL PERIKANAN TROPIS, 2020)
The handling of catches on ships in connection with capture fisheries in particular has the aim of preventing or reducing spoilage of fish and the possibility of a decline in the quality of the catch resulting in loss of selling prices. The main causes of the decline in the quality of the catch on the ship there are 5 factors namely how to handle, human resources, facilities, equipment, fishing units. Handling of catches on the ship with the puse seine Tangkap tool in PPN Sibolga based on calculations regarding the imbalance and suitability of the 5 factors handling on the purse seine ship namely handling methods, human resources, facilities, equipment and capture units found that the average value of conformity is by 78%, with the quality management policy in KEPMEN-52A/2013 which is an average of 78%, handling factors that can be fairly good.